Occurrence of PAHs in water samples of the Diep River, South Africa - Adetunji A Awe; Beatrice O Opeolu; Olatunde S Olatunji; Olalekan S Fatoki; Vanessa A Jackson; Reinette G Snyman (Water SA, 2020)
Occurrence of polycyclic aromatic hydrocarbons (PAHs) in freshwater may aggravate the water crisis currently being experienced in the Western Cape Province of South Africa. However, there is dearth of data on the levels of PAHs, which is necessary for effective assessment of water quality as well as remediation strategies. This study therefore assessed levels of PAHs in the Diep River freshwater system of Western Cape Province, South Africa. A liquid-liquid extraction solid-phase extraction gas chromatography flame ionisation detection (LLE-SPE-GC-FID) method was developed to simultaneously determine the 16 United States Environmental Protection Agency (USEPA) listed priority PAHs in water samples. The SPE-GC-FID method allowed an acceptable linearity (R2 > 0.999) within the calibration range of 1 to 50 µg/mL. Instrument detection limits ranged between 0.02 and 0.04 µg/mL and instrument quantification limits between 0.06 and 0.13 µg/mL. Recovery study results were also acceptable (83.69–96.44%) except for naphthalene, which had recovery of 60.05% in spiked water matrix. The seasonal averages of individual PAH detected at the studied sites ranged between not detected (nd) and 72.38 ± 9.58 µg/L in water samples.